An analytical investigation on the energy efficiency of integration of natural gas hydrate exploitation with H2 production (by in situ CH4 reforming) and CO2 sequestration. (15th July 2020) - Wang, Mengying; Deng, Chun; Chen, Hongnan; Wang, Xiaohui; Liu, Bei; Sun, Changyu; Chen, Guangjin; El-Halwagi, Mahmoud M.
Graphical abstract: Highlights: Modeling of new integrated system of gas hydrate exploitation with H2 production. Exergy analysis for integrated system and methane reforming subsystem was conducted. Techno-economic analysis of different injection-production scenarios were carried out. CO2 sequestration by integrated gas hydrate exploitation system can achieve 3914 kg/h. Abstract: Natural gas hydrate is considered as a new sustainable energy resource with huge potential and the increasing demand for green fuel hydrogen provides an opportunity for adopting alternative routines to produce hydrogen. The novel integrated system: natural gas hydrate exploitation by CO2 /H2 replacement integrated with in situ methane reforming, can simultaneously produce H2 and sequestrate CO2 . However, there is still a lack of in-depth research on the energy efficiency and economic performance of the novel integrated system. Therefore, we conducted a process design, modeling and simulation, exergy analysis, process integration, and sensitivity analysis of the integrated system for the first time. When the CO2 composition of the injected gas is 72 mol %, that is, the CH4 composition of the produced gas is 48.07 mol %, the exergy ratio of the integrated system after process integration is 1.54. The operating profit is 6.41 MM/y. The exergy efficiency of the methane reforming subsystem is 0.62. The CO2 emission from methane reforming subsystem can be sequestrated through the natural gas hydrate exploitation by CO2 /H2 replacement, achieving CO2 sequestration amount of 3914 kg/h with the CO2 sequestration ratio of 65%. The CO2 sequestration amount, CH4 composition in the produced gas, exergy ratio, and operating profit of the integrated system decrease as the CO2 composition of the injected gas decreases. Finally, sensitivity analysis results reveal that increasing the CH4 composition of the produced gas, minimizing water production, and increasing gas production in the exploitation unit will improve the energy performance of the novel integrated system. This work can guide the evaluation of energy efficiency and economy for the subsequent commercial exploitation of natural gas hydrate.